2018
DOI: 10.1371/journal.pone.0201656
|View full text |Cite
|
Sign up to set email alerts
|

Spanish adaptation and psychometric properties of the child version of the Cognitive Emotion Regulation Questionnaire

Abstract: BackgroundThe Cognitive Emotion Regulation Questionnaire for children (CERQ-k) is a useful clinical and research tool to identify cognitive patterns of emotion regulation that predict the presence of emotional symptomatology. This study aimed to validate the Spanish version of the CERQ-k (the CERQ-Sk) using a sample of children from Spain, which is not available.MethodsThe sample consisted of 582 children (48.6% girls) aged between 7 and 12 years (Mage = 9.49; SD = 1.2) recruited from Alicante, Spain. Cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
7
18
1
4
Order By: Relevance
“…Specifically, the results show that the strategies that present higher scores measured with the CERQ are Refocusing on planning and Putting into perspective, being these adaptive strategies, and those that present lower scores are Other blame and Self blame, which are maladaptive. These results are similar to those observed by Orgilés et al (2018) in a Spanish sample aged 7-12 years, who found that the strategy most used by children and adolescents was Refocusing on planning and the less used Other-blame.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Specifically, the results show that the strategies that present higher scores measured with the CERQ are Refocusing on planning and Putting into perspective, being these adaptive strategies, and those that present lower scores are Other blame and Self blame, which are maladaptive. These results are similar to those observed by Orgilés et al (2018) in a Spanish sample aged 7-12 years, who found that the strategy most used by children and adolescents was Refocusing on planning and the less used Other-blame.…”
Section: Discussionsupporting
confidence: 89%
“…To evaluate the validity of the translated version of the FEEL-KJ to measure the emotion regulation construct in our study, the scores of the participants in the FEEL-KJ factors have been correlated with the scores in the CERQ dimensions. The CERQ has been validated in the Spanish population (Dominguez-Sanchez et al, 2013;Orgilés et al, 2018), therefore statistically significant correlations among the scores of the FEEL-KJ factors and the scores of the CERQ dimensions in our sample would contribute to support the validity of the FEEL-KJ to measure emotion regulation. The scores in the FEEL-KJ factor of Adaptive Strategies correlated in a positively, statistically significant and moderately manner with the CERQ Adaptive dimension, r = 0.60, p < 0.01.…”
Section: Maladaptive Strategiesmentioning
confidence: 57%
See 3 more Smart Citations